Earthquake-Related Signals in Central Italy Detected by Hydrogeochemical and Satellite Techniques - Martinelli, Giovanni; Facca, Gianluca; Genzano, Nicola; Gherardi, Fabrizio; Lisi, Mariano; Pierotti, Lisa; Tramutoli, Valerio (Frontiers in Earth Science, 2020)
Central Apennines are one of the highest seismic risk regions in Italy. A number of energetic events (MW > 5) struck the region during the period 2004–2017, killing several hundreds of people (e.g., 294 casualties associated with the August 24th, 2016, MW 6.0 event of Amatrice). These earthquakes impacted piezometric levels, springs discharges, and groundwater chemistry across a large area, even at distances of dozens of kilometers from the epicenters. Here we present a multidisciplinary dataset based on hydrogeochemical and satellite observations associated with the seismic events that occurred in Central Italy during the period 2004–2017, which combines information derived from the application of groundwater monitoring and satellite techniques. Groundwater monitoring techniques allowed for the detection of hydrogeochemical anomalies in spring and well waters (14 water sampling points in total, with 22 variations larger than 2σ), while satellite techniques were applied to detect time-space variations in ground thermal emissions. We detected two significant, almost synchronous, anomalies in 2009 and 2016–2017 with both techniques, and we tentatively correlated them to crustal deformation processes. Part of the observed signals were detected before mainshocks, and they appear to be related to aseismic slip or to seismic slip eventually induced by minor fluctuations in seismicity. We argue that the combination of two factors, i.e., the shallow depth of local earthquakes and the concurrent deepening of groundwater circulation paths to several km depth, allow for the recording of variations in the stress field by geofluids released at the surface.